Birincil ve ikincil kaynaklardan farklı yöntemlerle altın ve gümüş kazanımı - Aydın, Şükriye Beste (Fen Bilimleri Enstitüsü, 2015)
Günümüzde altın fiyatlarındaki artış eğilimi ile Dünya'da olduğu gibi Türkiye'de de altın üretimine olan ilgi artmış ve yeni altın kaynakları bulma arayışına girişilmiştir. Türkiye'de altın-gümüş kazanımını siyanür liçi yöntemi ile yapan bir liç tesisinin siyanür kullanımından dolayı çevresel etki değerlendirmesi kapsamında yasal ve sosyal yükümlülükleri fazla olmakta ve bu sebepten birçok tesisin üretime geçmesinde problemler çıkabilmektedir. Altın mücevherat üretiminde Dünyada ilk sıralarda yer alan Türkiye, mücevherat üretimi sonrası oluşan çok miktarda altın hurdasına sahiptir. Bu hurdaların tekrar işlenmesi sırasında oluşan ve bilinen rafinasyon yöntemleri ile tekrar değerlendirilmesi mümkün olmayan curuflar bazı rafinasyon tesislerinde atık olarak saklanmakta iken bazı atölye çaplı işletmelerde ise siyanür liçi uygulanarak değerli metal kazanımı için tekrar işlem görmektedir. Şehir merkezlerinde bulunan bu işletmelerde siyanürün hiç bir iyileştirme çalışması yapılmadan kontrolsüz olarak atılması çevreye daha duyarlı olan yöntemlerin uygulanabilirliğinin araştırılmasını zorunlu kılmıştır. Tez kapsamında birincil ve ikincil kaynaklardan altın ve gümüş kazanımı liç ve flotasyon yöntemleri uygulanarak araştırılmıştır. Her iki yöntemin en yüksek altın ve gümüş verimlerini sağlayacak koşulları belirlenmiş ve uygulanabilirlikleri ekonomik ve çevresel şartlar değerlendirilerek incelenmiştir. Deneyler Çanakkale-Serçeler ve Çanakkale-Şahinli bölgelerinden alınan cevher numuneleri ve Onsa Rafineri'den temin edilen kuyumcu curufu ile gerçekleştirilmiştir. Çanakkale-Serçeler cevheri 18.85 ppm Au ve 120.00 ppm Ag, Çanakkale-Şahinli cevheri 4.72 ppm Au ve 7.79 ppm Ag, kuyumcu curufları ise 28.30 ppm Au ve 42.00 ppm Ag içermektedir. Çanakkale-Serçeler cevheri üzerinde yapılan flotasyon çalışmalarına göre, -74 µm tane boyutunda, kaba devrede 1000+1000 g/t Aerophine 3418 A+Aero 208 kullanımı ve 2 kademe temizleme devresi ile konsantrede %75.8 verim ile 625 ppm Au, %86.5 verim ile 4833 ppm Ag elde edilmiştir. Flotasyon kinetiğinin belirlenmesine yönelik yapılan çalışmalarda birinci derece ve ikinci derece kinetik modellerinin bu cevher için uygulanabilir olduğu tespit edilmiştir. Çanakkale-Serçeler cevheri ile yapılan liç deneylerinde ise en yüksek altın-gümüş çözünme verimleri -74 µm tane boyutu, %40 pülpte katı oranı ve 450 dev/dk karıştırma hızında 4 saatlik ön havalandırmadan sonra 2.44 g/L NaCN ilavesi ile 12 saatlik liç süresi sonunda elde edilmiştir. Bu koşullarda yapılan liç deneyleri sonucunda altın çözünme verimi %92.0, gümüş çözünme verimi ise %90.5 olarak bulunmuştur. Çanakkale-Serçeler cevheri ile ilgili yapılan maliyet analizine göre, bu cevherden altın-gümüş üretimi yapacak 500 t/gün kapasiteli bir flotasyon tesisinin cevher işleme maliyetinin 26.4 $/ton, aynı kapasiteli liç tesisinin cevher işleme maliyetinin ise 32.1 $/ton olduğu belirlenmiştir. Flotasyon yöntemi ile elde edilecek günlük net kâr 241,394 $, liç yöntemi ile elde edilecek günlük net kâr ise 327,376 $'dır. Çanakkale-Şahinli cevheri ile ilgili gerçekleştirilen flotasyon deneylerinde -74 µm tane boyutunda kaba devrede 250+250 g/t Aerophine 3418 A+Aero 208 kullanımı ve 4 kademeli temizleme devresi sonunda %76.3 kazanma verimi ile 437 ppm Au içerikli ve %58.5 kazanma verimi ile 511 ppm gümüş içeren konsantre elde edilmiştir. Çanakkale-Şahinli cevherinin flotasyon kinetiği incelenerek korelasyon katsayıları dikkate alındığında birinci ve ikinci derece kinetik modelinin uygulanabilir olduğu saptanmıştır. Çanakkale-Şahinli cevheri ile 450 dev/dk karıştırma hızı, 24 saat liç süresi, -74 µm tane boyutu, 1 g/L NaCN konsantrasyonu ve %40 pülpte katı oranında yapılan liç deneylerinin sonucunda altın %95.4 çözünme verimi ile, gümüş ise %88.9 çözünme verimi ile elde edilmiştir. Çanakkale-Şahinli cevheri için yapılan maliyet analizlerine göre 500 ton/gün kapasiteli bir altın-gümüş flotasyon tesisinin cevher işleme birim maliyetinin 19.2 $/ton, günlük net kârının 48,622 $, aynı kapasiteli liç tesisinin ise cevher işleme birim maliyetinin 25.9 $/ton, günlük net kârının 72,268 $ olduğu hesap edilmiştir. Çanakkale-Serçeler ve Çanakkale-Şahinli cevherlerine ait yapılan maliyet ve gelir analizleri değerlendirildiğinde liç yöntemi daha kârlı olmaktadır. Ancak siyanür liçi ile altın üretimi yapan tesislerin çevresel etki değerlendirmesi kapsamında yasal ve sosyal yükümlülüklerinin daha fazla olmasından dolayı bu durumun işletme maliyetlerine katacağı ek maliyetler siyanür liçi yönteminin ekonomikliğini azaltmaktadır. Bununla birlikte Çanakkale ili gibi ekolojik çevre özelliklerine sahip bir bölgede siyanür yönteminin yaratacağı çevresel baskılar gözönüne alındığında flotasyon yöntemi uygulanabilir olmaktadır. Kuyumcu curufunun flotasyonu ile ilgili çalışmalar sonucunda %89 verim ile 614.6 ppm altın ve %83.2 verim ile 886.3 ppm gümüş içeren konsantre -74 µm tane boyutunda, kaba devrede 600+600 g/t miktarında Aerophine 3418 A+Aerofloat 242 kullanımı ile malzemenin doğal pH'sı olan 10.8'de ve 4 kademeli temizleme devresi sonucunda elde edilmiştir. Flotasyon kinetiğinin belirlenmesine yönelik gerçekleştirilen deneylerde birinci ve ikinci kinetik modeline göre kinetik hız sabitlerinin hesap edilebileceği belirlenmiştir. Kuyumcu curufu ile ilgili olarak %10 pülpte katı oranında, 450 dev/dk karıştırma hızında, -53 µm tane boyutunda, 4 g/L NaCN konsantrasyonunda ve 24 saat liç süresinde yapılan liç deneylerinde %87.8 altın ve %81.5 gümüş çözünme verimlerine ulaşılmıştır. Kuyumcu curufları için liç yönteminde pülpte katı oranının arttırılması altın ve özellikle gümüş çözünme verimlerinde önemli düşüşlere sebep olmaktadır. Ancak endüstriyel açıdan %10 pülpte katı oranı ile çalışılamayacağından hesaplamalar tesisin %40 pülpte katı oranında çalışacağı varsayılarak yapılmıştır. Yılda 2000 ton üretimi olan kuyumcu curuflarının 6.6 ton/gün kapasiteli pilot ölçekli bir flotasyon tesisinde zenginleştirildiğinde curuf işleme birim maliyetinin 37.5 $/ton, günlük net kazancının ise 5,042 $ olacağı saptanmıştır. Aynı kapasiteli pilot ölçekli bir liç tesisinde ise curuf işleme birim maliyetinin 40.4 $/ton, günlük net kazancının ise 4,975 $ olacağı belirlenmiştir. Kuyumcu curufundan flotasyon yöntemi ile altın-gümüş kazanımının ekonomiye sağlayacağı katkı, atık bertarafı ve daha az maliyetli çevreye duyarlı yöntemlerin geliştirilmesi gibi olumlu etkiler dikkate alınarak flotasyon yönteminin siyanür liçi yöntemine göre daha uygun olduğu belirlenmiştir.

Nowadays, production and exploration of gold mineral have increased in importance in all over the world and as well as in Turkey, due to the increase in gold in prices. However, some difficulties are being experienced in taking the official permissions for cyanide usage. These permissions include environmental and social issues. Therefore, lots of companies cannot start operating in plant scale. Turkey is one of the most important jewellery producer in the world and for this reason, a large quantity of scrap gold exists in the country. These scrap golds can be reused in refining and slags are obtained after the process. But since this type of slags cannot be evaluated by the conventional refining methods, some of them are stored as tailings material and some of them are leached with cyanide in small scale plants. On the other side, these small plants, which are mostly located in city centers, do not apply any cyanide destruction processes. For this reason, the necessity of developing environmentally friendly methods have been investigated. The experiment conditions, which provided the maximum Au and Ag efficiency were determined applying leaching and flotation methods for primary and secondary sources within the scope of the thesis. Besides, the applicability of these methods was examined by evaluating both economic and environmental conditions. The experiments were carried out with the ore samples taken from the Serçeler and Şahinli regions of Çanakkale and the jewellery slag sample taken from a refinery. According to the results of the chemical analyses, while the Çanakkale-Serçeler ore sample contains 18.85 ppm Au and 120.0 ppm Ag, the Çanakkale-Şahinli ore sample has 4.72 ppm Au and 7.79 ppm Ag. On the other hand, the jewellery slag sample contains 28.3 ppm Au, 42.0 ppm Ag. The mineralogical analyses were performed on the polished section samples employing QEMSCAN (Quantitative Evaluation of Minerals by Scanning Electron Microscopy) for Çanakkale-Serçeler and Çanakkale-Şahinli ores. Regarding to the jewellery slag sample, the minerological analysis was done by MLA (Mineral Liberation Analyzer), using search mode for generating particle data and line mode for model minerology. According to mineralogical analysis, the Çanakkale-Serçeler ore sample was dominated by pyrite, quartz, and kaolinite. Au-Ag occurrences in the ore sample were observed as native gold (95-100% Au and 0-5% Ag), argentian native gold (80-95% Au and 5-15% Ag), electrum (20-80% Au and 20-80% Ag), calaverite (AuTe2, 37% Au), chlorargyrite (AgCl), argentite (Ag2S), and jalpaite-proustite (Ag3CuS2-Ag3AsS3). The Çanakkale-Şahinli ore sample was dominated by quartz (75.6% by mass), feldspars (9.3% by mass) and pyrite (6.2% by mass) while the remaining was kaolinite and muscovite. The detected electrum grains were practically liberated. The jewellery slag sample was composed of mostly amorphous silica material with high amounts of Ca and Na. The gold and silver appeared as metalic. The effect of particle size, collector type and amount were investigated in flotation tests for the Çanakkale-Serçeler ore sample. To determine the optimum particle size, the flotation experiments were performed for 150 µm, 100 µm, 74 µm, 53 µm, and 38 µm particle size fractions. However, a significant difference was not observed in the results and the optimum particle size was determined as 74 µm. The best recovery of Au and Ag were obtained as 75.8% with 625 ppm Au content and 86.5% with 4833 ppm Ag content, respectively, when 1000 g/t+1000 g/t Aerophine 3418 A+Aero 208 were used as collectors in ten stages rougher flotation and two stages cleaning flotation. The studies conducted for determining the flotation kinetics showed that the first order and second order kinetic models were found to be applicable for the Çanakkale-Serçeler ore. The leaching behaviour of a sulphide gold-silver ore obtained from the Canakkale-Serçeler Region sample was investigated in terms of a relationship between gold and silver extractions and cyanide consumption. 95% Au and 88.0% Ag extractions were obtained under the determined conditions as 24 h leaching duration, -74 µm particle size, 40% solids ratio, 4 g/L NaCN concentration, and 450 rpm stirring speed with NaCN consumption of 3.35 g/L. Since the NaCN consumption was higher than in industrial applications, Pb(NO3)2 and H2O2 additions and aeration using an air pump were tested during leaching in order to decrease the consumption. While Pb(NO3)2 addition with aeration caused a decrease in the metal extractions, the individual or combined additions of H2O2 and aeration could not provide a reduction in the cyanide consumption. Therefore, the effect of the pre-aeration followed by cyanidation was tested. Eventually, applying 4 h of pre-aeration before a shorter leaching duration of 12 h provided 92.0% Au and 90.5% Ag extractions with a lesser NaCN consumption of 2.44 g/L. According to cost analysis carried out on the Çanakkale-Serçeler ore, while the ore processing unit cost for a 500 t/d capacity flotation plant was found as 26.4 $/t, the ore processing unit cost of the leaching plant with the same capacity was found as 32.1 $/t. Besides, daily net profit of flotation plant and leaching plant were calculated as 241,394 $ and 327,376 $ respectively. The flotation concentrate of the Çanakkale-Şahinli ore sample containing a gold content of 437 ppm with recovery of 76.3% and a silver content of 511 ppm with recovery of 58.5% was obtained with the following conditions: 74µm particle size 250 + 250 g / t Aerophine 3418 A + Aero 208, and applying 4 stages cleaning flotation. In the leaching tests performed as systematic for the Çanakkale-Şahinli ore sample, the influence of leaching parameters such as leaching duration, NaCN concentration, particle size, and solids ratios were examined. The optimum leaching parameters were determined as 24 h leaching duration, -74 µm particle size, 40% solid ratio, 1 g/L NaCN, and 450 rpm stirring speed under atmospheric conditions With the optimum leaching parameters, the highest Au and Ag recoveries were obtained as 95.4% Au and 88.9% Ag respectively. When flotation kinetics was examined by considering correlation coefficients it was determined that first and second kinetic model were found to be applicable for the Çanakkale-Şahinli ore. According to cost analysis carried out on the Çanakkale-Şahinli ore, the ore processing unit cost and daily net profit for a 500 t/d capacity flotation plant were determined as 19.2 $/t and 48,622 $ as the ore processing unit cost and daily net profit of the leaching plant with the same capacity were found as 25.9 $/t and 72,268 $ respectively. When the cost analyses of the Serçeler and Şahinli ore samples were evaluated, leaching method was found to be more economical. However, the official permissions realted with the environmental and social issues cause extra costs for the cyanidation plants. Therefore, the feasibility of leaching plants decreases. Furthermore, flotation method has become prominent in a region like Çanakkale, which is a natural host for various ecological species. In the flotation experiments of the jewellery slag, the concentrate, which had gold content of 614.6 ppm with recovery of 89.0% and silver content of 511 ppm with recovery of 83.2%, was obtained with 74µm particle size by adding 600 + 600 g/t Aerophine 3418 A + Aero 208 in rougher stage and applying 4 stages cleaning flotation. Besides, it was determined that the kinetic constant could be found by applying the first or the second kinetic model in the experiments performed for the flotation kinetics. To investigate the optimum leaching condition of the jewellery slag, the experiments were performed. As a result of the experiments, the highest Au and Ag recoveries were achieved as 87.8% and 81.5%, respectively with the following conditions: 10% solids ratio, 4 g/L NaCN, -53 µm particle size, 24 h cyanidation time, and 450 rpm stirring speed under atmospheric conditions. The increase of solids ratio caused a significant decrease in gold and particularly silver recoveries. Even though highest recoveries were obtained at 10% solids ratio, the leaching is usually performed at higher solids ratios between 35% and 50% in industrial applications. Therefore, 40% solids ratio was chosen for economical evaluation. When jewellery slag, which was produced 2000 ton per year, was enriched at a pilot-scale flotation plant for 6.6 ton/day capacity, slag processing unit cost was found as 37.5 $/t and daily net profit was calculated as 5,042 $. On the other hand slag processing unit cost was found as 40.4 $/t and daily net profit was calculated as 4,975 $ at a pilot-scale leaching plant for same capacity. Gold-silver enrichment from the jewellery slag by flotation method provided positive effect as contributing economically, waste disposal and developing of less profitable and environment-friendly methods. When these effects were considered, it was determined that flotation method was more suitable than leaching method.
Gold and silver recovery from primary and secondary sources with different processes
Tez (Doktora)-- İTÜ Fen Bilimleri Enstitüsü, 2015
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Maden Mühendisliği ve Madencilik; Altın Geri dönüşümü; Gümüş Geri dönüşümü; Cüruf; Mining Engineering and Mining; Gold Recycling; Silver Recycling; Slag